2016
DOI: 10.1186/s41121-016-0002-x
|View full text |Cite
|
Sign up to set email alerts
|

From pulpal stem cells to tooth repair: an emerging field for dental tissue engineering

Abstract: In current dental practices, traditional restorative approaches may have relatively limited long-term survival and may be associated to diverse complications, such as allergy, pulpitis, or periodontal pathologies. To overcome these shortcomings, novel innovative strategies have been envisioned for tooth repair. During the two last decades, the extensive advances in our understanding of tooth development as well as stem cell research provide the foundation for exciting opportunities in dental tissue engineering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…It is reported that it is easier for cells to perform amoeboid movement through fibrous scaffolds, giving higher proliferation rates. [43][44][45][46][47] It is noteworthy that in these cases, the aspect of discussion of chemical effects on the cells and thereby their biological activity remains untouched. Therefore, elutes were prepared for the indirect contact test, as recommended by the ISO.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that it is easier for cells to perform amoeboid movement through fibrous scaffolds, giving higher proliferation rates. [43][44][45][46][47] It is noteworthy that in these cases, the aspect of discussion of chemical effects on the cells and thereby their biological activity remains untouched. Therefore, elutes were prepared for the indirect contact test, as recommended by the ISO.…”
Section: Discussionmentioning
confidence: 99%
“…SCAPs, derived from the human apical papilla of growing tooth roots, 50 are a significant population of MSCs in endodontics regeneration 51 . The SCAP cultures can differentiate into odontoblast‐like cells with potential proliferation and mineralization 52 .…”
Section: Dental Stem Cells In Dentin Regenerationmentioning
confidence: 99%
“…Endodontic therapy is fraught with challenges, such as complexity and variability in root canal anatomy, microbial challenges, handling complications, and addressing patient-related factors that significantly impact treatment outcomes and necessitate careful consideration and expertise. Recently, stem-cell-based regeneration of odontogenic tissues has gained popularity due to its non-invasive nature [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%